Dzień Spółdzielczości. (Starogard : [s.n.], 1946)
Afisz inf. o uroczystościach wraz z programem 29.09.1946 r.
Keywords: Spółdzielnie -- Polska -- Starogard Gdański -- 1945-1970 -- druki ulotne; Starogard Gdański (Polska) -- 1945-1970 -- druki ulotne